1985
DOI: 10.1002/pd.1970050302
|View full text |Cite
|
Sign up to set email alerts
|

Five cases of prenatally diagnosed sex chromosome mosaicism

Abstract: Prenatal detection of chromosome mosaicism is a relatively rare phenomenon and always constitutes a diagnostic problem. The difficulties are much more when the mosaics involve the sex chromosomes, because of the large phenotypic variability in individuals with these abnormalities. We studied 5 cases of true mosaics, 4 of these were prenatally detected, while 1 case was revealed only in the fetal lymphocytes after induced abortion. The limits of amniotic fluid culture with regard to the diagnosis of true mosaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Postnatal lymphocyte and skin cultures showed 16-74 per cent 45,X cells. The case reported by Nocera et al, (1985) is also not included since only 45,X cells were found in the prenatal analysis. The pregnancy was terminated and a female abortus presented with Turner syndrome stigmata including 'streak' ovaries and coarctation of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal lymphocyte and skin cultures showed 16-74 per cent 45,X cells. The case reported by Nocera et al, (1985) is also not included since only 45,X cells were found in the prenatal analysis. The pregnancy was terminated and a female abortus presented with Turner syndrome stigmata including 'streak' ovaries and coarctation of the aorta.…”
Section: Discussionmentioning
confidence: 99%